The Review Jurnal: Potensi Tepung Pisang Dan Tepung Sukun Sebagai Bahan Baku Pembuatan Beras Analog - Permata Sari, Nilam Ariyanti; Kusumayanti, Heny; Yusran, Fakhri Farghani (Peneliti.net, 2026)
This study explores the potential use of kepok banana flour and breadfruit starch as raw materials for analog rice production. Analog rice is a food innovation designed to support dietary diversification in Indonesia, offering adjustable nutritional composition. Banana and breadfruit flours are rich in carbohydrates, fiber, and minerals, with higher nutritional values compared to regular rice flour. Gelatin, a protein derived from animal collagen, is also added to improve the physical and nutritional properties of the final product. The analog rice is produced using an extrusion method that involves formulation, preconditioning, extrusion, and drying. Results show that analog rice made from banana flour and breadfruit starch has high protein and fiber content and a low glycemic index, making it suitable for people with diabetes. Utilizing these local ingredients not only benefits public health but also supports the national food security program and offers economic advantages by increasing the market value of local agricultural products